A novel PGPF Penicillium olsonii isolated from the rhizosphere of Aeluropus littoralis promotes plant growth, enhances salt stress tolerance, and reduces chemical fertilizers inputs in hydroponic system - Tarroum, Mohamed; Romdhane, Walid Ben; Al-Qurainy, Fahad; Ali, Ahmed Abdelrahim Mohamed; Al-Doss, Abdullah; Fki, Lotfi; Hassairi, Afif (Frontiers in Microbiology, 2022)
In this study, the fungal strain (A3) isolated from the rhizosphere of the halophyte plant Aeluropus littoralis was identified as Penicillium olsonii based on sequence homology of its ITS region. The A3 fungus was shown to be halotolerant (up to 1M NaCl) and its optimal growth was at 27°C, but inhibited at 40°C. In liquid culture medium, the A3 produced indole acetic acid (IAA) especially in the presence of L-tryptophan. Tobacco plants grown under hydroponic farming system were used to evaluate the promoting activity of the direct effect of A3 mycelium (DE) and the indirect effect (IDE) of its cell-free culture filtrate (A3CFF). The results showed that for the two conditions (DE or IDE) the tobacco seedlings exhibited significant increase in their height, leaf area, dry weight, and total chlorophyll content. Interestingly, the A3CFF (added to the MS liquid medium or to nutrient solution (NS), prepared from commercial fertilizers) induced significantly the growth parameters, the proline concentration, the catalase (CAT) and the superoxide dismutase (SOD) activities of tobacco plants. The A3CFF maintained its activity even after extended storage at 4°C for one year. Since the A3 is a halotolerant fungus, we tested its ability to alleviate salt stress effects. Indeed, when added at 1:50 dilution factor to NS in the presence of 250 mM NaCl, the A3CFF enhanced the plant salt tolerance by increasing the levels of total chlorophyll, proline, CAT, and SOD activities. In addition, the treated plants accumulated less Na+ in their roots but more K+ in their leaves. The A3CFF was also found to induce the expression of five salt stress related genes (NtSOS1, NtNHX1, NtHKT1, NtSOD, and NtCAT1). Finally, we proved that the A3CFF can reduce by half the chemical fertilizers inputs. Indeed, the tobacco plants grown in a hydroponic system using 0.5xNS supplemented with A3CFF (1:50) exhibited significantly higher growth than those grown in 0.5xNS or 1xNS. In an attempt to explain this mechanism, the expression profile of some growth related genes ( (NR1, NRT1, TRYP1, YUCCA6-like), DET2, DWF4) was performed. The results showed that all these genes were up-regulated following plant treatment with A3CFF.